In Silico Discovery of Novel Drug and Vaccine Targets in Chlamydia abortus Through Subtractive Genomics - Ali, Zainab Oun; Al-Asadi, Sura; Abdul Wahhab, Batool Hazim; Rampurawala, Jamila (The Iraqi Journal of Veterinary Medicine, 2025)
Chlamydia abortus is a Gram-negative bacterium that causes chlamydiosis, a zoonotic disease leading to abortions and stillbirths in livestock and posing significant public health risks. With rising antimicrobial resistance and limited treatment efficacy, there is a pressing need for novel, targeted therapeutics to mitigate its economic and zoonotic impact. This study employed a subtractive genomics approach to analyze the complete proteome of C. abortus (strain DSM 27085 / S26/3), aiming to identify essential, non-host homologous proteins involved in unique bacterial metabolic pathways. Out of 932 proteins, five integral membrane proteins YidC, YajC, SecY, CAB503, and CAB746 were selected based on their essentiality, pathogen-specific roles, and absence of host homology. Anti-target screening confirmed no similarity to host proteins, ensuring minimal off-target effects. Antigenicity prediction (VaxiJen > 0.4) identified YidC, YajC, SecY, and CAB503 as strong vaccine candidates, while CAB746 exhibited variable antigenicity across species. Conservancy analysis showed YidC and YajC were highly conserved across C. abortus strains, while the others displayed strain-specific variations. Domain analysis revealed conserved motifs (e.g., IPR002208 in SecY) and transmembrane regions, supporting their structural and immunological relevance. In conclusion, YidC, YajC, SecY, CAB503, and CAB746 represent promising drug and vaccine targets. Their bacterial specificity, immunogenicity, and safety profile warrant further experimental validation to support targeted interventions against chlamydiosis‎‎‎.